PEMIKIRAN KH. M. HASYIM ASY’ARI TENTANG HAK DAN KEWAJIBAN SUAMI ISTRI - Masrokhin; M. Rizki Syahrul Ramadhan (LPPM UNHASY, 2023)
‘Ulamā has different opinions about the varians and the technicals the rights and obligations for husband and his wife. In Indonesia, that differences could be find in the literature-work of Indonesian’s ‘ulamā such as Ḍaw’ al-Miṣbāḥ fī Bayān Aḥkām al-Nikāḥ, the work of KH. M. Hasyim Asy’ari. Consider to the established of istinbāṭ theory in uṣūl al-fiqh, this research asking question about “How the method of istinbāṭ al-aḥkām of KH. M. Hasyim Asy’ari in deciding the rights and obligations for husband and his wife?” Keywords: Thought, KH. M. Hasyim Asy’ari, Right and Obligation, Husband and Wife Daftar Pustaka Asy’ari, Muhammad Hasyim. 2017. Ḍaw’ al-Miṣbāḥ fī Bayān Aḥkām al-Nikāḥ. Jombang: Pustaka Tebuireng _______________________. t.th. Risālah Ahl al-Sunnah wa al-Jamā'ah fī Bayān al-Musammāh bi Ahl al-Sunnah wa al-Jamā'ah. Jombang: Maktabah Turāth al-Islāmī. _______________________. t.th. Al-Tibyān fī al-Nahy 'an Muqātha'ah al-Arḥām wa al-Aqārib wa al-Ikhwān. Jombang: Maktabah Turāth al-Islāmī. _______________________. 1415 H. Ziyādah Ta'līqāt 'alā Manẓūmah al-Shaykh ‘Abd Allāh Yāsīn al-Fāsuruwānī. Jombang: Maktabah al-Turāth al-Islāmī. Badawi, Syansuri. 2004.Uṣūl al-Fiqh. Jombang: Majelis Ilmi Pesantren Tebuireng. Hadziq, Muhammad Ishomuddin. t.th. Irshād al-Sārī. Jombang: Maktabah al-Turāth al-Islāmī. __________________________, 1999. KH. Hasyim Asy’ari, Figur Ulama dan Pejuang Sejati. Jombang: Pustaka Warisan Islam. Khuluq, Lathiful. 2018. Tafsir Pemikiran Kebangsaan dan Keislaman Hadratussyaikh KH. M. Hasyim Asy’ari. Jombang: Pustaka Tebuireng. Masrokhin. 2017. Sejarah Hidup Hadratus Syaikh KH. Muhammad Hasyim Asy’ari dalam Supratno, Haris, dkk. Pemikiran Hadratus Syaikh KH. Muhammad Hasyim Asy’ari. Surabaya: Unesa University Press. Palmer, Donald. 2006. Looking at Philosophy: The Unbearable Heaviness of Philosophy Made Lighter. New York: McGraw-Hill. Rusyd, Ibn. t.th. Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid. Surabaya: Al-Hidayah, Sābiq, Al-Sayyid. 2009. Fiqh al-Sunnah. Kairo: al-Fatḥ li al-I’lām al-‘Arabī. Saebani, Beni Ahmad. 2011. Filsafat Hukum Islam. Bandung: Pustaka Setia. Shahab, Muhammad Asad. 1971. al-‘Allāmah Muḥammad Hāshim Ash’arī Waḍi’ Lubnah Istiqlāl Indūnīsiyā. Bairut: Dār al-Ṣadiq. Al Amin, Habibi.